Opinion On Drug Information Services Provided In A Multi- Specialty Teaching Hospital - Vijayakumar TM, Poovi G & Dhanaraju MD (Archives of Global Professionals, 2011)
Objective: To evaluate the various drug information queriesreceived, and to access the drug information services providedby the pharmacy practice department.Method: Drug information queries received during wardrounds, direct communication, telephone or internet etc. weredocumented in the drug information request anddocumentation forms prepared by the department over theperiod of January 2010 to June 2010. Various parameters likestatus of enquirer, their specialty, mode of receipt of query,purpose of query, type of query etc. were consider forevaluation.Results: Out of 208 queries received, major 56 (26.9%) frommale medical ward. Maximum [82 (39.4 %)] queries were fromthe physicians. 73 (35.0 %) of the queries were about therecent advances and the updating of the information, It wasfound that mostly the mode of request was during wardrounds 85 (40.9%). Most of the queries [126 (60.6%)] wereanswered by written or printout format. Majority of thequeries [195 (93.8 %)] were answered directly to theenquirers through direct access. Most of the queries wereanswered through books in the department [86 (41.3 %)].Conclusion: Results of the external auditing revealed thatrequestors were generally satisfied with the service provided.The drug information services provided by clinical pharmacistsat the hospital were found to be useful and beneficial to thehealthcare professionals and patients.